HOW DOES PERCEIVED CONTROL INFLUENCE IMPACT OF EMOTIONS ON HEALTH? - Fernández Castro, Jordi; Edo Izquierdo, Silvia (Anales de Psicología / Annals of Psychology)
The aim of this paper is to show that perceived control concept is essential to analyze the relationship between emotions and health. Objetive control, perceived control, and personal control concepts are discussed. A distinction between general beliefs about control and specific self-efficacy expectancies is made. A hypothesis about perceived control modulation of psychobiological reactions in emotional states is formulate.